Mekanisme Penyaluran Dana Alokasi Khusus (DAK) Fisik dan Dana Desa Melalui Kantor Pelayanan Perbendaharaan Negara Dumai pada Wilayah Bayar Kabupaten Bengkalis - Yuliana Syahfitri; Endang Sri Wahyuni (Politeknik Negeri Bengkalis, 2020)
This study aims to describe the mechanism for disbursing Physical Spesific Allocation Funds and Village Funds and revealing problems that arise in the implementation of disbursing Physical and Village Allocation Funds at the Dumai State Treasury Service Office in the pay areas of Bengkalis Regency. This type of research is a qualitative descriptive approach to data checking and interpretation. Data collection techniques performed consisted of interviews and documentation.Â The data analysis technique used is descriptive analysis. The results of this study indicate that the mechanism for the distribution of Physical Spesific Allocation Fund at the State Treasury Service Office is carried out in stages, at the same time, and at the same time as a recommendation. The disbursement of Physical Spesific Allocation Funds which is carried out in stages consists of three phases, in phase I distributed at the latest in February and no later than July 2019 at 25%, at stage II distributed at the fastest in April and no later than 31 October 2019 at 45%, and in stage III it is distributed as much as the difference between the amount of funds that have been distributed up to stage II. Then for the Distribution of Village Funds is also carried out in stages, in phase I distributed the fastest in January and no later than June 2019 at 20%, in phase II it will be distributed the fastest in March and no later than 21 July 2019 by 40%, and phase III will be distributed the fasted in July until the end of the fiscal year in December by 40%.